Perencanaan Komunikasi Humas Bawaslu Kabupaten Malaka Dalam Mengoptimalkan Pengelolaan Informasi Pemilu Melalui Media Sosial Facebook - Bria, Metriana; Tuhana, Veki Edizon; Jelahut, Felisianus Efrem (Jurnal Dakwah Tabligh, 2024)
Planning in communication has an important role in a process that involves organizational goals or objectives, developing a comprehensive strategy to achieve the set targets. The aim of this research is firstly to find out the public relations communication planning of the Malaka Regency Bawaslu in optimizing the management of election information via social media, secondly to find out the Malaka Regency Bawaslu’s public relations communication planning is an important factor in optimizing the management of the election information via Facebook social media, and thirdly to find out Malaka Regency Bawaslu’s efforts to optimize the management of election information via Facebook social media were analyzed using the Four Step Public Relations theory. The research method used is qualitative with a case study approach. The data collected in this research show that the Malaka Regency Bawaslu’s public relations communication planning is carried out by determining problems, preparing programs, communicating, and conducting program evaluations. Good communication planning by the Malaka Regency Bawaslu public relations is very important in managing election information via Facebook social media because it can ensure accurate, transparent, and coordinated dissemination of election information via Facebook social media, and Facebook social media is a supporting factor in disseminating information by utilizing the media. Facebook social media as a communication medium and a medium for exchanging information with the public. The Malaka Regency Bawaslu’s efforts are to supervise the election process with the hope that the elections in Malaka regency can run according to applicable regulations and that election violations do not occur, and the Malaka Regency Bawaslu serves the community as needed by sharing all election-related information with the public via the social media Facebook.